PENYELENGGARAAN PELAYANAN PUBLIK YANG BERKUALITAS SEBAGAI UPAYA MEMBERIKAN PELAYANAN PRIMA KEPADA MASYARAKAT - Abdul Yuli Andi Gani, Mr. (Jurnal Ilmiah Administrasi Publik, 2012)
Societal demand in the decentralization era toward qualified public service has grown rapidly. Government credibility is highly determined by its ability to cope with various problems of public service. Thus, a capable government would gain more and more support from the people to provide satisfying public service. The quality of service should become all partiesâ concern within the government either in the implementation or leadership level in accordance with its role. Regional government needs an integrated management within its administration particularly in licensing service. The service would highly depend on 3 (three) aspects, those are the implementation pattern, human resources support, and institution /organization. Therefore, to improve the service, order, mechanism, and implementation procedures for taskforce is needed.